2013
DOI: 10.1038/ajg.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Lipids With Colorectal Adenomas

Abstract: In this large cross-sectional study, higher levels of serum triglycerides were significantly associated with an increasing prevalence of both non-advanced and advanced colorectal adenomas, while higher levels of ApoA-1 and HDL cholesterol were significantly associated with an increasing prevalence of non-advanced adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 29 publications
6
87
2
Order By: Relevance
“…However, the standard protocol recommends that screening is initiated after the age of 50 years. Previous studies have suggested that there is a certain degree of correlation between metabolic syndrome and colorectal adenoma, a precancerous lesion of CRC (12)(13)(14), our study aimed to develop a risk determinant for younger patients who may benefit from screening on the basis of their metabolic profiles and associated clinical history. The general adenoma detection rate of 20% for both sexes, 23% in males and 17% in females, is in line with standard quality indicators in colonoscopic practice (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the standard protocol recommends that screening is initiated after the age of 50 years. Previous studies have suggested that there is a certain degree of correlation between metabolic syndrome and colorectal adenoma, a precancerous lesion of CRC (12)(13)(14), our study aimed to develop a risk determinant for younger patients who may benefit from screening on the basis of their metabolic profiles and associated clinical history. The general adenoma detection rate of 20% for both sexes, 23% in males and 17% in females, is in line with standard quality indicators in colonoscopic practice (15).…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies were conducted in the USA (20,39) , one in Germany (19) , three in Korea (9,10,22) and three in Japan (28,29,36) ( Table 2). The results from nine studies showed that serum TC had a significant association with risk of CRA (RR = 1·04; 95 % CI 1·01, 1·09, P = 0·02) and there was no significant heterogeneity among these studies (Q = 5·26, P value for heterogeneity = 0·73, I 2 = 0 %; Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population included 20,500 consecutive participants undergoing colonoscopy as part of routine health check-up examinations at the Center for Health Promotion of the Samsung Medical Center in Seoul, Korea, from January 2006 to June 2009 (9). If a participant had more than one colonoscopy during the study period, we included only the first colonoscopy.…”
Section: Study Populationmentioning
confidence: 99%